An efficient hybrid LC-S compensation topology for wireless power transfer system - Irshad, Talha; Nauman, Malik; Abas, Pg Emeroylariffion (Institute of Advanced Engineering and Science, 2024)
Wireless power transfer (WPT) system is gaining prominence for charging various applications, including electric vehicles, biomedical implants, smartphones, and network sensors. Efficient compensation networks are essential to minimize leakage inductance. The performances of single-element compensation topologies are compared based on different coupling and loading conditions, revealing that series-series (SS) and series-parallel (SP) topologies exhibit lower peak efficiencies of 85% and 90%, respectively, than parallel-series (PS) and parallel-parallel (PP) topologies, having 99% and 98.5% peak efficiency, respectively; with efficiencies deteriorating under different loading and coupling conditions. To address these shortcomings, a hybrid inductor-capacitor capacitor (LC-S) compensation topology is proposed, outperforming the single element topologies and maintaining over 95% efficiency under varying loading and coupling conditions. A slight efficiency drop to 82% due to frequency splitting was observed with low load resistance. In terms of the output characteristics, the LC-S topology achieved 1.2 W. These results showcase the potential of the LC-S topology for enhancing WPT system efficiency.